A Review of Flipped Classroom and Cooperative Learning Method Within the Context of Vygotsky Theory - Erbil, Deniz Gökçe (Frontiers in Psychology, 2020)
In the flipped classroom method, which is accepted as one of the blended learning approaches, the traditional teaching process takes place outside of the classroom through videos. Activities, projects and homework related to upper-level cognitive field steps are carried out during classroom time. Research and interest in the flipped classroom are increasing steadily. Employing a cooperative learning method is suggested for using class time in the flipped classroom method. However, there has not been sufficient research on the implemented results of those suggestions. Moreover, there is no clear roadmap on how to incorporate cooperative learning methods into the flipped classroom. This research reviews theoretical infrastructures of flipped classroom and cooperative learning methods according to the Vygotsky theory, and makes various suggestions for implementation and implementers.